Value Creation Strategy in Tourism : An Islamic Perspective - Fani Firmansyah (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2017)
The international tourism industry now is becoming an increasingly competitive marketplace. Understanding the needs, interests and behaviors of different tourist markets plays a critical role in support them to destinations. Given the fast growth in the number of tourists and despite the great Muslim population worldwide. It is important to develop appropriate marketing strategies. To develop tourism prospects sharia government could use such a marketing strategy, marketing for instance, marketing mix and segmenting, targeting and positioning (STP). The marketing mix is a set of marketing tools used by a state or a company to continue achieving its marketing objectives in target market. STP is the most important initial step in identifying customer value. It is expected from the use of this strategy could make sharia tourism as a market leader in the field of tourism and also could attract more tourists to visit and increase economic returns of state.